When Is Foreign Exchange Intervention Effective? Evidence from 33 Countries - Marcel Fratzscher; Oliver Gloede; Lukas Menkhoff; Lucio Sarno; Tobias Stöhr (American Economic Journal: Macroeconomics, 2019)
This paper examines foreign exchange intervention based on novel daily data covering 33 countries from 1995 to 2011. We find that intervention is widely used and an effective policy tool, with a suc cess rate in excess of 80 percent under some criteria. The policy works well in terms of smoothing the path of exchange rates, and in stabilizing the exchange rate in countries with narrow band regimes. Moving the level of the exchange rate in flexible regimes requires that some conditions are met, including the use of large volumes and that intervention is made public and supported via communication.
Keywords: E52; E58; F31; F33; O19; O24; 330